FEATURES OF COMPENSATION FOR DAMAGE CAUSED BY THE TAX AUTHORITIES AND THEIR OFFICIALS - Алпысбай Дюсембаевич, Жусупов (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2015)
This article describes the features of redress, the establishment of a legal regime in which the damage to be compensated at the expense of the treasury, significantly increases the efficiency of the Institute of redress, as it provides citizens and organizations as taxpayers faster and more reliable source of payment, timely protection and complete recovery of social justice.